Akulturasi Budaya Hukum dalam Pendidikan Anti Korupsi bagi Siswa Sekolah - Setyo Pamungkas; Selvie Novitasari; Sri Harini Dwiyatmi; Yonathan Imananta; Marsela Dorthea Maabuat (CV Rewang Rencang, 2024)
Anti-corruption is a fundamental principle that serves as the foundation for social movements within society. It emerges from the need to build a safeguard against the widespread concern over massive deviant behaviors that violate the law—namely, corruption. The anti-corruption movement aims to encourage proactive behaviors in preventing corrupt acts. For school students, this movement is introduced as anti-corruption education, which essentially broadens their understanding of corruption as a factual legal issue within society. From the perspective of legal culture, anti-corruption education creates space to instill law-abiding behaviors in specific groups within society, fostering a legal culture that promotes compliance with existing laws. The legal culture approach to anti-corruption through education is adopted because corruption has become a cultural behavior, perceived as normal in various institutions, raising concerns about ethical conduct in society. Embedding an anti-corruption legal culture in schools is a process of integrating early legal compliance with counter-corruption behaviors, aiming to establish a new culture—one that fosters anti-corruption attitudes from an early age. This is the essence of legal cultural acculturation, which intervenes in negative social behaviors to develop legal awareness as a fundamental aspect of a law-abiding society.